2009
DOI: 10.1016/j.cedpsych.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon effects in homework research: The homework–achievement association depends on the measures used and the level of analysis chosen

Abstract: Using a data set specifically tailored to homework research, with a sample of 1,275 students from 70 classes in Switzerland, the association between homework and achievement in French as a second language was tested at three levels (class level, between-student level, withinstudent level). The strength and direction of the homework-achievement association depended on the homework indicator chosen and differed to some degree across analytical levels. At the class level, achievement was higher in classes set fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 36 publications
10
62
0
9
Order By: Relevance
“…On one hand, it aligns with the studies of Dettmers et al (2011) andTrautwein et al (2009) which showed that indeed negative emotions during homework predict negative achievement.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On one hand, it aligns with the studies of Dettmers et al (2011) andTrautwein et al (2009) which showed that indeed negative emotions during homework predict negative achievement.…”
Section: Discussionsupporting
confidence: 88%
“…This investigation extends the scope of previous research in primary and secondary education (Dettmers et al, 2011;Goetz et al, 2012;Trautwein et al, 2009) to look at the role of learning-related emotions in predicting achievement outcomes in the first year of university. To our best knowledge, only few studies in first year samples tried to prove similar relations (Tempelaar et al, 2012;.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…En relación con la variable tiempo también existe una gran discrepancia, mientras unos encuentran que la relación entre esta variable y el rendimiento es positiva (Cooper, 1989;, otros encuentran que es débil o negativa (De Jong, Westerhof, & Creemers, 2000;Tam, 2009;Trautwein, Schnyder, Niggli, Neumann, & Lüdtke, 2009). Estos resultados inconsistentes, quizás se expliquen si tenemos en cuenta la tercera variable, el aprovechamiento del tiempo, ya que dedicar más tiempo a los deberes no significa emplear estrategias eficientes de gestión de los mismos (Xu, 2007).…”
unclassified